Analisis SWOT (strengths, weaknesses, opportunities, threats) pusat informasi dan konseling remaja (pik-remaja) - Nurochim Nurochim (Jurnal Konseling dan Pendidikan, 2021)
This study aims to describe an analysis of the strengths, weaknesses, opportunities and threats of the Youth Information and Counseling Center program (PIK-Remaja). This study uses a literature review method, in the form of scientific reports published in reputable national and international journals. The strength of the PIK-Remaja program is that it is a program designed with peer counseling as and integrated with social and religious institutions. The weakness of this program is the ineffective and inefficient socialization, as well as the commitment of all stakeholders in supporting the program. Opportunities for this program are policies that support coordination between central and regional governments for guidance and funding. The challenge for the PIK-Remaja program is the demographic conditions of the population and adolescents who are surrounded by globalization and technological developments.